2021
DOI: 10.1101/2021.02.02.21250988
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 specific T cell responses are lower in children and increase with age and time after infection

Abstract: SARS-CoV-2 infection of children leads to a mild illness and the immunological differences with adults remains unclear. We quantified the SARS-CoV-2 specific T cell responses in adults and children (<13 years of age) with RT-PCR confirmed asymptomatic and symptomatic infection for long-term memory, phenotype and polyfunctional cytokines. Acute and memory CD4+ T cell responses to structural SARS-CoV-2 proteins significantly increased with age, whilst CD8+ T cell responses increased with time post infection. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…These studies support a relevant role for structural N protein as an immune target in SARS-CoV-2 infection. We found robust antibody responses in children both to the S RBD as well as to the N protein, while Weisberg et al (9) found antibodies to the S, but not the N protein; and Cohen et al (37) found lower responses in children in general. These differences, as well as a lower response to the S protein in general in our sample, may reflect differences in HLA between American and Brazilian populations, or even a difference in immunization history, given a tradition in vaccination program for children in Brazil.…”
Section: Discussionmentioning
confidence: 43%
“…These studies support a relevant role for structural N protein as an immune target in SARS-CoV-2 infection. We found robust antibody responses in children both to the S RBD as well as to the N protein, while Weisberg et al (9) found antibodies to the S, but not the N protein; and Cohen et al (37) found lower responses in children in general. These differences, as well as a lower response to the S protein in general in our sample, may reflect differences in HLA between American and Brazilian populations, or even a difference in immunization history, given a tradition in vaccination program for children in Brazil.…”
Section: Discussionmentioning
confidence: 43%
“…These studies support a relevant role for structural N protein as an immune target in SARS-CoV-2 infection. We found robust antibody responses in children both to the S RBD as well as to the N protein, while Weisberg et al (9) found antibodies to the S, but not the N protein; and Cohen et al (38) found lower responses in children in general. These differences, as well as a lower response to the S protein in general in our sample, may reflect differences in HLA between American and Brazilian populations, or even a difference in immunization history, given a tradition in vaccination program for children in Brazil.…”
Section: Discussionmentioning
confidence: 45%
“…In a recent larger cohort study, children and adolescents showed high and durable antibody responses to SARS-CoV-2, following mild or asymptomatic infection [62]. Regarding cell-mediated immunity, only a few reports describe a lower or similar magnitude of SARS-CoV-2-specific T cells in children [21,57,63]. As the magnitude of the adaptive immune response to SARS-CoV-2 is related to severity of symptoms, it is essential that studies compare adults and children with similar clinical presentations.…”
Section: Immune Response To Sars-cov-2 Infection In Childrenmentioning
confidence: 99%